Law Enforcement in Criminal Acts Regional Head Elections (Pilkada) 2020 in Binjai City by Center Integrated Law Enforcement - Lailatus Sururiyah (Indonesian Journal Education, 2025)
Law enforcement is an important aspect that must be considered in the implementation of regional head elections. Bawaslu, the police, and the Prosecutor's Office at all levels must work together to oversee the regional head election process so that it takes place honestly and fairly. The 2020 regional head elections (Pilkada) in Binjai City were held amid the COVID-19 pandemic and experienced several violations, including election crime violations, resulting in several handling of election crime violations by the Election Integrated Law Enforcement Center (Sentra Gakkumdu). Criminal violations during the 2020 regional election campaign period were the most common offenses, including those related to the neutrality of State Civil Apparatus (ASN).